Sulforaphane protects cardiomyoblasts against chemical hypoxia by increasing mitochondrial-ER communication and autophagy - Gabriela Navarrete-Anastasio; Edith Álvarez-León; Angélica Ruiz-Ramírez; Elizabeth Soria-Castro; Wylly Ramsés García-Niño; Israel Pérez-Torres; Rebeca López-Marure; Cecilia Zazueta; Alejandro Silva-Palacios (Chemico-Biological Interactions, 2026)

Reproductive biology of the starry grouper, Epinephelus labriformis ( Perciformes: Serranidae ): Gonadal development, sex change and sexual pattern - Rebeca Sánchez‐Cardenas; Josué López‐Cardiel; Juan Manuel Martínez‐Brown; Luis Antonio Rendón‐Martínez; Rodrigo Martínez‐Moreno; Leonardo Ibarra‐Castro (Journal of Fish Biology, 2026)
The reproductive biology of the starry grouper, Epinephelus labriformis , in Mazatlan Bay, Mexico, was studied through histological analysis of the gonads. A total of 527 fish were examined through weekly sampling from March 2017 to March 2018. In this species, the gonads are bilobed and connected to a common gonoduct. E. labriformis exhibits monandric protogynous hermaphroditism, with a female‐to‐male proportion of 1.5 females:1 male in fully mature animals. In females, six ovarian phases were identified, and the oogenic cycle was analysed in 314 females, classified as asynchronous. The gonadosomatic index increased from 0.13 in the immature phase to 3.35 at maturity, declining to 1.16 post‐spawning. Transforming testes ( n = 95) revealed four stages of sex change, during which ovarian tissue is progressively replaced by testicular tissue. Males and transforming individuals appeared in larger size classes, with no females recorded beyond 27.5 cm total length ( L t ). Females reach sexual maturity at 17.2 cm L t . In comparison, males mature at 19.42 cm L t . Sex change occurs in individuals with total lengths ranging from 20 cm to 33.5 cm L t , with an average size for sex change of 24.7 cm. Our findings define the reproductive strategy of E. labriformis . They also provide actionable guidelines for fisheries management in Mexico. In the absence of specific regulations in Mexico, we recommended establishing a minimum catch size between 24 and 27 cm L t and seasonal protection during the reproductive period to preserve spawning potential and maintain a balanced sex ratio in the population.

Enhancing sulfate-rich wastewater treatment through polyvinyl alcohol -immobilized sulfidogenic granules: Optimization of reactor configuration and bioaugmentation strategies - Rebeca Castro; Lorenz Adrian; Gemma Gabriel; David Gabriel; Xavier Gamisans; Xavier Guimerà (Journal of Environmental Chemical Engineering, 2026)

High-dose neonatal riboflavin remodels energy metabolism and brain mitochondrial ultrastructure in rats exposed to maternal high-fat diet - Eulália Rebeca Silva-Araújo; Ana Elisa Toscano; Osmar Henrique dos Santos Júnior; Joaci Pereira dos Santos Júnior; Paula Brielle Pontes; Dyego Maia de Oliveira; Henrique José Cavalcanti Bezerra Gouveia; Maria Luísa Oliveira Buarque Silva; Eduardo Padrón-Hernández; Raul Manhães-de-Castro (Food Research International, 2026)

Regulatory role of annexin A1 in NLRP3 inflammasome activation in atopic dermatitis: insights from keratinocytes in human and murine studies - Rebeca D. Correia-Silva; Mab P. Corrêa; Maria Eduarda de Castro; Joaquim S. Almeida; Solange C. G. P. D’Ávila; Sonia M. Oliani; Karin V. Greco; Cristiane D. Gil (Journal of Molecular Medicine, 2025)

Eeg Microstates and Balance Parameters for Stroke Discrimination: A Machine Learning Approach - Eloise de Oliveira Lima; José Maurício Ramos de Souza Neto; Felipe Leonardo Seixas Castro; Letícia Maria Silva; Rebeca Andrade Laurentino; Vitória Ferreira Calado; Isolda Maria Barros Torquato; Karen Lúcia de Araújo Freitas Moreira; Suellen Marinho Andrade (Brain Topography, 2025)

Quercetin preserves mitochondria-endoplasmic reticulum contact sites improving mitochondrial dynamics in aged myocardial cells - Ray Jiménez; Alejandra Zúñiga-Muñoz; Edith Álvarez-León; Wylly Ramsés García-Niño; Gabriela Navarrete-Anastasio; Elizabeth Soria-Castro; Israel Pérez-Torres; Elizabeth Lira-Silva; Natalia Pavón; Alfredo Cruz-Gregorio; Rebeca López-Marure; Cecilia Zazueta; et al. (Biogerontology, 2025)

Trypanosoma cruzi has Two Peptidyl-tRNA Hydrolases Showing Different Localization and Function - María Elizabeth Reséndiz-Juárez; Ana Laura Rosas-Soto; Armando Pérez-Rangel; José Tapia-Ramírez; Emmanuel Ríos-Castro; Fanny Rodríguez-Cruz; Ricardo Alejandre-Aguilar; Rebeca Manning-Cela; Gloria León-Avila; José Manuel Hernández-Hernández (Acta Parasitologica, 2025)

Magnetic nanostructured agents for the mitigation of mycotoxins and cyanotoxins in the food chain - Jesús M. González-Jartín; Lisandra de Castro Alves; Y. Piñeiro; Amparo Alfonso; Rebeca Alvariño; Manuel González Gomez; Mercedes R. Vieytes; J. Rivas; Luis M. Botana (Food Chemistry, 2024)

Detection of Brucella S19 Vaccine Strain DNA in Domestic and Wild Ungulates from Brazilian Pantanal - Gabriel Carvalho de Macedo; Carolina Santos Pereira Cardoso Trindade; Caroline Paes dos Santos; Luiz Gustavo Rodrigues Oliveira Santos; Filipe Martins Santos; William Oliveira de Assis; Alinne Pereira de Castro; Emily Rebeca Antunes Gonçalves; Sávio Freire Bruno; Heitor Miraglia Herrera; Carina Elisei de Oliveira (Current Microbiology, 2024)

Retrieving the real microbial diversity in aquatic plastisphere - Igor Taveira; Rebeca O. Castro; Jefferson Cypriano; Henrique F. Santos; Fernanda Abreu; Fábio V. de Araújo (Marine Pollution Bulletin, 2024)

Use of otolith microchemistry signatures to assess the habitat use of Centropomus undecimalis in lagoon systems of the southwest Atlantic - Paulo Roberto Camponez de Almeida; Marcus Rodrigues da Costa; Rebeca Dias de Souza Coutinho; Ana Méndez-Vicente; Jorge Pisonero Castro; Cassiano Monteiro-Neto; Rafael de Almeida Tubino; Alberto Teodorico Correia (Regional Studies in Marine Science, 2024)

Development of a flow-cell bioreactor for immobilized sulfidogenic sludge characterization using electrochemical H2S microsensors - Rebeca Castro; Gemma Gabriel; David Gabriel; Xavier Gamisans; Xavier Guimerà (Chemosphere, 2024)

Widespread Coral Bleaching and Mass Mortality of Reef-Building Corals in Southern Mexican Pacific Reefs Due to 2023 El Niño Warming - Andrés López-Pérez; Rebeca Granja-Fernández; Eduardo Ramírez-Chávez; Omar Valencia-Méndez; Fabián A. Rodríguez-Zaragoza; Tania González-Mendoza; Armando Martínez-Castro (Oceans, 2024)
In May 2023, oceanic and atmospheric anomalies indicated El Niño conditions in the eastern Pacific, followed by coral bleaching in coral communities and reefs of Huatulco. We conducted surveys and sampled coral reef communities from late June to mid–August of 2023 to evaluate the intensity and extent of the changes associated with the warming event. From January of 2023, Huatulco experienced positive sea surface temperature (SST) anomalies; however, beginning in June, the high-temperature anomalies became extreme (>31 °C; ~2 °C above historical records). These high temperatures resulted in extensive coral bleaching in middle–late June and mortality from middle–late July (>50–93%). In addition, the area experienced significant reductions in echinoderm abundance and fish biomass. In 2023, severe bleaching affected coral systems in the Central Mexican Pacific, Gulf of Mexico, and Mexican Caribbean, making this the most devastating marine heatwave event, simultaneously impacting coral reefs across Mexico’s Pacific and Atlantic coasts.

Antileshimania, anti- Trypanosoma cruzi and antimicrobial activities of scandenin and 4'-O-methylderrone from Deguelia costata - Rebeca Lopes Santos; Lilian da Silva Miguêz; Julyanna Oliveira Castro; Izaltina Silva-Jardim; Tanira Matutino Bastos; Karoline Almeida Felix de Sousa; Milena Botelho Pereira Soares; Amancio José de Souza; Aiane Nascimento Santana; Andreza Santos de Jesus; Madson de Godoi Pereira; Lourdes Cardoso de Souza Neta (Natural Product Research, 2023)

Early Neolithic human remains from Galería del Sílex in Sierra de Atapuerca, Burgos, Spain - Antonio Molina-Almansa; Mercedes Conde-Valverde; Ana Isabel Ortega; Rebeca García-González; Laura Rodríguez; Alfonso Alday; Eneko Iriarte; Salvador Domingo; Juan Luis Arsuaga; José María Bermúdez de Castro; Eudald Carbonell; José Miguel Carretero; et al. (Quaternary Science Reviews, 2023)

Sulforaphane modifies mitochondrial-endoplasmic reticulum associations through reductive stress in cardiomyocytes - Alejandro Silva-Palacios; Dana Arana-Hidalgo; Zaira Colín-Val; Vicente Castrejón-Téllez; Elizabeth Soria-Castro; José Pedraza-Chaverrí; Rebeca López-Marure; Cecilia Zazueta (Chemico-Biological Interactions, 2023)

A letter to the editor about the article “The modularity codes” - Omar Paredes; Elsa Magaña-Cuevas; Sorpresa Lora-Castro; Juan D. Serna-Grilló; D.Y. De la Mora; Diana Ríos Patiño; Rebeca Romo-Vázquez; J. Alejandro Morales (Journal of Theoretical Biology, 2023)

Corrigendum to “Relationship between thermal environment, thermoregulatory responses and energy metabolism in goats: A comprehensive review” Journal of Thermal Biology 109 (2022) 103324] - Ana Rebeca Castro Lima; Robson Mateus Freitas Silveira; Maria Samires Martins Castro; Laura Bertolaso De Vecchi; Angélica Santos Rabelo de Souza Bahia; Thaise Pinto de Melo; Márcia Helena Machado da Rocha Fernandes; Kléber Tomás Resende (Journal of Thermal Biology, 2023)

Antiparasitic efficacy of dietary administration of trichlorfon (Masoten®) in the control of Neoechinorhynchus buttnerae (Neochinorhynchidae) in Colossoma macropomum (Serrasalmidae) - Liliane Araújo Castro; Sanny Maria Andrade-Porto; Rebeca Guimarães Oliveira; Yasmin Luzeiro Batista; Felipe Moura Araújo Silva; Christiane Patrícia Feitosa Oliveira; Elizabeth Gusmão Affonso; Claudinei Cruz; Marcos Tavares-Dias (Aquaculture International, 2021)

Metal(loid) exposure on children from a historical metallurgical site - Javier Castro-Larragoitia; Ofelia Morton-Bermea; Rebeca Yasmín Pérez-Rodríguez; Israel Razo-Soto; Isidro Montes-Ávila; Elizabeth Hernández-Álvarez; Ángel Alberto Arellano-Álvarez (Environmental Geochemistry and Health, 2021)

Mercury in Blood of Children Exposed to Historical Residues from Metallurgical Activity - Ofelia Morton Bermea; Javier Castro-Larragoitia; Ángel Alberto Arellano Álvarez; Rebeca Jazmín Pérez-Rodríguez; Adriana Leura-Vicencio; Benedetto Schiavo; Elías Salgado-Martínez; Israel Razo Soto; Elizabeth Hernández Álvarez (Exposure and Health, 2021)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

A New Design Criterion to Improve the Intact Stability of Galician Small Fishing Vessels - Jesús Alvite-Castro; José A. Orosa; Diego Vergara; Ángel M. Costa; Rebeca Bouzón (Journal of Marine Science and Engineering, 2020)
The first technical factor involved in maritime accidents is related to the lack of intact stability. The current stability criterion, based on fixing a minimum value for each of the different static and dynamic righting arms, is not regarded as satisfactory. Correspondingly, a new criterion based on the transverse metacentric height, dynamic stability up to 70° heel, and critical wave height were considered for fishing vessels less than or equal to 24 m in length. This can be understood as an improvement on the Rahola criterion or an equivalent criterion of dead ship capsize mode, as assumed in the second-generation stability criteria. The proposed criterion, when used in a real case study on the Galician fishing grounds, achieved higher precision. The few vessels that did not comply with the proposed requirement can continue to operate in the area if the Meteorological and Oceanographic Coefficient (CMO) is considered at the time we employ our criteria. As a result, their activity is limited to only a few fishing grounds where adequate weather conditions exist. Finally, the methodology developed can be easily extrapolated to other regions in the world.

β-Catenin Role in the Vulnerability/Resilience to Stress-Related Disorders Is Associated to Changes in the Serotonergic System - Emilio Garro-Martínez; Rebeca Vidal; Albert Adell; Álvaro Díaz; Elena Castro; Josep Amigó; Raquel Gutiérrez-Lanza; Eva Florensa-Zanuy; Laura Gómez-Acero; M. Mark Taketo; Ángel Pazos; Fuencisla Pilar-Cuéllar (Molecular Neurobiology, 2020)

Targeting β-Catenin in GLAST-Expressing Cells: Impact on Anxiety and Depression-Related Behavior and Hippocampal Proliferation - Rebeca Vidal; Emilio Garro-Martínez; Álvaro Díaz; Elena Castro; Eva Florensa-Zanuy; Makoto M. Taketo; Ángel Pazos; Fuencisla Pilar-Cuéllar (Molecular Neurobiology, 2019)

Potential of Bacterial Isolates from a Stream in Manaus-Amazon to Bioremediate Chromium-Contaminated Environments - Ydrielly Veras Teles; Lorena Mota de Castro; Ézio Sargentini Junior; Aryana Pinheiro do Nascimento; Henrique Alves da Silva; Rebeca Silveira Costa; Rayane Delmontes do Nascimento Souza; Adolfo José da Mota; José Odair Pereira (Water, Air, & Soil Pollution, 2018)

Cerebellar Transcranial Direct Current Stimulation (ctDCS) Impairs Balance Control in Healthy Individuals - Águida Foerster; Lorena Melo; Marina Mello; Rebeca Castro; Lívia Shirahige; Sérgio Rocha; Kátia Monte-Silva (The Cerebellum, 2017)

Allocation trade‐offs dominate the response of tropical forest growth to seasonal and interannual drought - Christopher E. Doughty; Yadvinder Malhi; Alejandro Araujo-Murakami; Daniel B. Metcalfe; Javier E. Silva-Espejo; Luzmila Arroyo; Juan P. Heredia; Erwin Pardo-Toledo; Luz M. Mendizabal; Victor D. Rojas-Landivar; Meison Vega-Martinez; Marcio Flores-Valencia; et al. (Ecology, 2014)
What determines the seasonal and interannual variation of growth rates in trees in a tropical forest? We explore this question with a novel four‐year high‐temporal‐resolution data set of carbon allocation from two forest plots in the Bolivian Amazon. The forests show strong seasonal variation in tree wood growth rates, which are largely explained by shifts in carbon allocation, and not by shifts in total productivity. At the deeper soil plot, there was a clear seasonal trade‐off between wood and canopy NPP, while the shallower soils plot showed a contrasting seasonal trade‐off between wood and fine roots. Although a strong 2010 drought reduced photosynthesis, NPP remained constant and increased in the six‐month period following the drought, which indicates usage of significant nonstructural carbohydrate stores. Following the drought, carbon allocation increased initially towards the canopy, and then in the following year, allocation increased towards fine‐root production. Had we only measured woody growth at these sites and inferred total NPP, we would have misinterpreted both the seasonal and interannual responses. In many tropical forest ecosystems, we propose that changing tree growth rates are more likely to reflect shifts in allocation rather than changes in overall productivity. Only a whole NPP allocation perspective can correctly interpret the relationship between changes in growth and changes in productivity.

Mycoses and Antifungals: reviewing the basis of a current problem that still is a biotechnological target for marine products - Luciana Terra; Paula A. Abreu; Valéria L. Teixeira; Izabel C. P. Paixão; Rebeca Pereira; Bruno Leal; André Luiz Lourenço; Pabulo H. Rampelotto; Helena C. Castro (Frontiers in Marine Science, 2014)